Porous boron nitride nanofibers enhanced sodium acrylate and acrylamide copolymer hydrogels for effective adsorption of Pb2+. Issue 5 (13th January 2023) - Gao, Xiangqian; Huang, Xindi; Lin, Jing; Yu, Chao; Tang, Chengchun; Huang, Yang
Abstract : A new composite hydrogel adsorbent for adsorption of Pb 2+ has been prepared by combining porous boron nitride nanofibers (BNNFs) and the acrylamide and sodium acrylate copolymer (P(AANa- co -AM)) via a chemical crosslinking method. Abstract : A new composite hydrogel adsorbent for adsorption of Pb 2+ has been prepared by combining porous boron nitride nanofibers (BNNFs) and the acrylamide and sodium acrylate copolymer (P(AANa- co -AM)) via a chemical crosslinking method. Porous BNNFs with abundant hydroxyl functional groups can form hydrogen bond interactions with carboxyl and amino functional groups of the copolymer in the composite hydrogel and carry and dissipate forces for the composite hydrogels. So the mechanical performances of the copolymer hydrogels can be effectively improved, which is very valuable for the practical application of the composite hydrogel to remove Pb 2+ from waste water. The thermal stability and swelling performance of the pure copolymer hydrogels were also greatly improved. This is not only because of the strong hydrogen bond interactions but also the good thermal stability and flexibility of BNNFs. The composite hydrogel adsorbent shows superior adsorption capacity for Pb 2+ (490.2 mg g −1 ) to most of the reported hydrogel adsorbents. The chemisorption dominates the whole adsorption process according to the pseudo-second-order kinetic and the Langmuir models. The composite hydrogel adsorbent also shows good reusability. Therefore, we believe that the prepared composite hydrogels will play an important role in removing Pb 2+ from wastewater.